Mental Health and Wellbeing in the Anthropocene A Posthuman Inquiry - Mcphie, Jamie (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book makes the unorthodox claim that there is no such thing as mental health. It also deglamourises nature-based psychotherapies, deconstructs therapeutic landscapes and redefines mental health and wellbeing as an ecological process distributed in the environment - rather than a psychological manifestation trapped within the mind of a human subject. Traditional and contemporary philosophies are merged with new science of the mind as each chapter progressively examples a posthuman account of mental health as physically dispersed amongst things - emoji, photos, tattoos, graffiti, cities, mountains - in this precarious time labelled the Anthropocene. Utilising experimental walks, play scripts and creative research techniques, this book disrupts traditional notions of the subjective self, resulting in an Extended Body Hypothesis - a pathway for alternative narratives of human-environment relations to flourish more ethically. This transdisciplinary inquiry will appeal to anyone interested in non-classificatory accounts of mental health, particularly concerning areas of social and environmental equity - post-nature.